2016
DOI: 10.1051/matecconf/20166813012
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model for the Effects of Perceived Indoor Work Environment on Sick Building Syndrome and Stress

Abstract: Abstract. Sick Building syndrome (SBS) and stress have a prevalent influence on organizational productivity and competitiveness. Unhealthy employees not only tend to have high medical leaves but also low productivity due to ailments and discomforts. Studies that investigate the effects of indoor work environment on Sick Building Syndrome (SBS) have yielded mixed results while their effect on stress has not been empirically established. Furthermore, studies that simultaneously investigate both SBS and stress ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Their results showed that indoor working environment, air quality and emotional stress were highly correlated with SBS, which has a vital role in improving IEQ to reduce emotional stress and alleviate SBS. 10 Nor Hazana Abdullah et al 11 conducted a survey of indoor environment and stress. Their results showed that the indoor working environment had a significant effect on SBS, and there was a strong significant relationship between SBS and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that indoor working environment, air quality and emotional stress were highly correlated with SBS, which has a vital role in improving IEQ to reduce emotional stress and alleviate SBS. 10 Nor Hazana Abdullah et al 11 conducted a survey of indoor environment and stress. Their results showed that the indoor working environment had a significant effect on SBS, and there was a strong significant relationship between SBS and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have always felt the need to improve quality of life, and pursuing this goal also meant optimizing the surroundings where we develop an activity, whether for work, leisure or rest. There is a close relationship between the elements involved in a building, such as where it is located, the building materials used, the orientation of the housing, the presence of power lines, etc., and the health or physical and psychological balance of the people who occupy it (Abdullah, Hamid, Shaif, Shamsuddin and Wahab, 2016).…”
Section: Introductionmentioning
confidence: 99%